2020
DOI: 10.1128/msphere.00858-19
|View full text |Cite
|
Sign up to set email alerts
|

Coimmunoprecipitation with MYR1 Identifies Three Additional Proteins within the Toxoplasma gondii Parasitophorous Vacuole Required for Translocation of Dense Granule Effectors into Host Cells

Abstract: Toxoplasma gondii is a ubiquitous, intracellular protozoan that extensively modifies infected host cells through secreted effector proteins. Many such effectors must be translocated across the parasitophorous vacuole (PV), in which the parasites replicate, ultimately ending up in the host cytosol or nucleus. This translocation has previously been shown to be dependent on five parasite proteins: MYR1, MYR2, MYR3, ROP17, and ASP5. We report here the identification of several MYR1-interacting and novel PV-localiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 52 publications
4
53
0
Order By: Relevance
“…One crucial linchpin of gene expression that the parasite targets is c-Myc, a central regulator capable of controlling more than 15% of the genes in the mammalian genome (6). Previous genetic screens showed that upregulation of c-Myc is dependent on a number of Toxoplasma genes, including four dubbed "Myc regulatory" genes (MYRs) (7). In all cases, however, these MYR genes were shown to be necessary for the translocation of many GRA effectors across the PVM, rather than encoding the protein directly controlling c-Myc upregulation.…”
mentioning
confidence: 99%
“…One crucial linchpin of gene expression that the parasite targets is c-Myc, a central regulator capable of controlling more than 15% of the genes in the mammalian genome (6). Previous genetic screens showed that upregulation of c-Myc is dependent on a number of Toxoplasma genes, including four dubbed "Myc regulatory" genes (MYRs) (7). In all cases, however, these MYR genes were shown to be necessary for the translocation of many GRA effectors across the PVM, rather than encoding the protein directly controlling c-Myc upregulation.…”
mentioning
confidence: 99%
“…6). Interestingly, as we were studying the interactome of GRA44, we learned of ongoing work in John C. Boothroyd's lab showing a physical and functional interaction between MYR1 and GRA44 (34). MYR1 was initially identified through a forward genetic screen for Toxoplasma mutants unable to activate host c-Myc and translocate effectors, such as GRA16 and GRA24 (22).…”
Section: Discussionmentioning
confidence: 99%
“…A fourth protein, the secreted parasitic kinase ROP17, is also required for translocation [ 108 ]; ROP17 is likely to phosphorylate one or more of the components of the MYR translocon and thus potentially energize translocation. Recently, three additional proteins, MYR4, GRA44, and, GRA45, were also identified as essential for the export of GRA effectors in Toxoplasma [ 109 ]. GRA44 is a putative phosphatase, while GRA45, predicted to contain a small heat shock protein domain and a transthyretin-like domain, is critical in preventing other GRA effectors from aggregating and thus functions as a chaperone (Wang Y. et al, 2019. bioRxiv doi:10.1101/867705) ( Figure 10 , Figure S7 ).…”
Section: Secretion Across the Parasitophorous Vacuole In Other Apimentioning
confidence: 99%
“…All MYR translocon proteins (MYR1-4, ROP17, GRA44, and GRA45) identified in Toxoplasma gondii have orthologues in other apicomplexan parasites, such as Neospora caninum and Hammondia hammondi , although the levels of sequence divergence suggest rapid evolutionary pressure [ 10 , 106 , 109 ]. However, no homologues of MYR proteins have been identified in Sarcocystis (also an Eucoccidioridia) or the more distantly related Plasmodium; thus, MYR proteins appear somehow restricted to a subset of Coccidia, perhaps as an adaptation to the rapid evolution of their specific effectors and life cycle (host cell).…”
Section: Parasitic Vacuolar Secretion Pathways As Drug Targetsmentioning
confidence: 99%
See 1 more Smart Citation